RISK FACTORS OF ADVERSE EFFECTS IN ACTIVE PULMONARY TUBERCULOSIS PATIENTS WITH CATEGORY 1 TREATMENT - Zulfa, Ilil Maidatuz (Acta Holistica Pharmaciana, 2019)
Category 1 treatment of active pulmonary tuberculosis (TB) takes 6-8 months that can expose patients to adverse effects. The severity of adverse effects occur can affects patients adderence that lead to loss to follow-up. The recent study was aimed to analyze risk factors that might have contribution to the occurence of adverse effects in active pulmonary TB patients received category 1 treatment. A cross sectional study with open questionnaire was conducted to active pulmonary TB patients who undergo treatment follow-up at RS Paru Karang Tembok Surabaya. Gender, ages, diabetes melitus status, body weight, and length of treatment were analyzed as potential risk factors of the number of adverse effects occur through poisson regression The result derived from 41 patients analyzed showed that gender (OR: 0,842, 95% CI: 0,550-1,287, p>0,05), ages (OR: 0,997, 95% CI: 0,986-1,009, p>0,05), body weight (OR: 0,992, 95% CI: 0,976-1,010, p>0,05), diabetes melitus status (OR: 1,197, 95% CI: 0,773-1,856, p>0,05), and length of treatments (OR: 1,007, 95% CI: 0,989-1,025, p>0,05) have no significant risk to the number of adverse effects patients suffered from In the present study , gender, age, body weight, diabetes mellitus status, and the length of TB treatments have being taken have no significant contribution to the number of adverse effects occured. However, further study with higher sample size to confirm the result need to be conducted.